Imaging in Appendicular Diverticulosis with Appendicitis - Patil, Aruna R.; Chaudhari, Bhushan; Godhi, Satyajit; Shivakumar, Swarna (Journal of Gastrointestinal and Abdominal Radiology, 2020)
Appendicular diverticulosis (AD) is an extremely rare condition. They are either incidentally detected in a normal or inflamed appendix or as diverticulitis manifesting clinically as appendicitis. It is commonly a radiological or pathological diagnosis. On computed tomography (CT), AD can mimic focal perforation. There are reported associations between AD and appendicular adenocarcinoma. This case reports the classical features of AD on CT with background appendicitis.
Keywords: appendix; diverticulosis; computed tomography